Lipid Profile and Ultrasonographic Grading in Alcoholic and Non Alcoholic Fatty Liver Patients - Shahi, A.; Gautam, N.; Rawal, S.; Sharma, U.; Jayan, A. (Kathmandu University Medical Journal, 2021)
Background Fatty liver disease (FLD) is a common and major chronic liver disease. It has been implicated that patients have disorders of lipid metabolism and are involved in the pathogenesis of fatty liver. Hence, it was designed to observe the association between lipid profile and fatty liver disease. Objective This study was undertaken to evaluate the association of lipid profile status, hemoglobin and albumin levels with fatty liver disease patients diagnosed based on ultrasonography (USG). Method This Cross-sectional study was undertaken in the Department of Internal Medicine with the collaboration of the Department of Radiology and Department of Biochemistry, Universal College of Medical Sciences-Teaching Hospital (UCMS-TH), Bhairahawa, Nepal from March 2019 to February 2020 in a total of 100 patients diagnosed with fatty liver disease by ultrasonography. The fasting blood was collected for lipid profile and carried out in the automated analyzer following standard protocol. Result In 100 cases, the male to female ratio was 1.8:1. Fifty six percent of the total cases presented with alcoholic fatty liver disease (AFLD) while the remaining 44% with non-alcoholic fatty liver disease (NAFLD). The spectrum of lipid abnormality was observed with increased total cholesterol (TC), Low Density Lipoprotein (LDL), increased triglycerides (TG), Very Low Density Lipoprotein (VLDL) in alcoholic fatty liver disease cases as compared to non-alcoholic fatty liver disease cases. However, it has been observed that TG/HDL and Non-HDL/HDL were higher in non-alcoholic fatty liver disease as compared to alcoholic fatty liver disease. Moreover, a statistically significant difference was observed in HDL between AFLG2 and NAFLG2 (p-value: 0.012). Conclusion Dyslipidemia and decreased HDL have been implicated in fatty liver diseases. USG in conjunction with Non-HDL/HDL, TG/HDL, hemoglobin, and albumin can be useful in early screening and monitoring of dyslipidemia in fatty liver patients.